2018
DOI: 10.1038/gim.2017.162
|View full text |Cite
|
Sign up to set email alerts
|

Clinical whole-exome sequencing for the diagnosis of rare disorders with congenital anomalies and/or intellectual disability: substantial interest of prospective annual reanalysis

Abstract: PurposeCongenital anomalies and intellectual disability (CA/ID) are a major diagnostic challenge in medical genetics-50% of patients still have no molecular diagnosis after a long and stressful diagnostic "odyssey." Solo clinical whole-exome sequencing (WES) was applied in our genetics center to improve diagnosis in patients with CA/ID.MethodsThis retrospective study examined 416 consecutive tests performed over 3 years to demonstrate the effectiveness of periodically reanalyzing WES data. The raw data from ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
143
1
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 161 publications
(153 citation statements)
references
References 43 publications
5
143
1
4
Order By: Relevance
“…Additionally, two studies were published supporting the advantage of reanalysis. Nambot et al reported 15.4% definitive results after reanalyzing 156 initially reported negative cases. Half of these cases ( n = 12) were solved due to new publications that either implicate new causative genes or allowed reclassification of variants.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, two studies were published supporting the advantage of reanalysis. Nambot et al reported 15.4% definitive results after reanalyzing 156 initially reported negative cases. Half of these cases ( n = 12) were solved due to new publications that either implicate new causative genes or allowed reclassification of variants.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, 11 cases classified as nondiagnostic in this study were ultimately clinically diagnosed with multiple system atrophy, cerebellar type, and another case was identified with a VUS associated with increased risk for this condition (Gilman et al, ; Zhao et al, ). We also reclassified variants from our previously reported 76 cases (Fogel et al, ) based on current annotation, which has been shown to improve diagnosis over time (Alfares et al, ; Ewans et al, ; Fogel, ; Fogel, Lee, Strom, Deignan, & Nelson, ; Fogel et al, ; Nambot et al, ; Rexach et al, ; Wright et al, ). This resulted in four cases previously classified as nondiagnostic or having a reportable VUS being reclassified with a pathogenic/likely pathogenic genetic variant.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA was extracted from the buccal swab using a standard phenol‐chloroform procedure. Exome capture and sequencing and the resulting libraries were sequenced using the methods previously described in Nambot et al Complete exome sequencing (ES) section can be found in the Supporting Information and methods. The identified variant was validated by Sanger sequencing with forward 5′‐TGTTTCTGCCTTCCCCTCAT‐3′ and reverse 5′‐TGGGAAGCCTCAGGAAGAAG‐3′ polymerase chain reaction (PCR) primers.…”
Section: Methodsmentioning
confidence: 99%